G protein-coupled receptors in prostate cancer: research progress and therapeutic targets - Xiong, Wei; Zhou, Bingpeng; Shi, Jian; Ni, Dong; Xiong, Zhiyong (Frontiers in Cell and Developmental Biology, 2025)
Prostate cancer (PCa) is one of the most common cancers of male genitourinary system, with castration-resistant prostate cancer (CRPC) posing a major therapeutic challenge. G protein-coupled receptors (GPCRs), the largest family of cell surface receptors, are increasingly recognized as critical regulators of tumor progression, metastasis, and therapy resistance. This review summarizes the research progress of orphan receptors, chemokine receptors and hormone-sensitive receptors of GPCRs in PCa. We highlight how these receptors modulate key oncogenic processes such as androgen receptor (AR) signaling, cell proliferation, migration, and immune evasion. Emerging therapeutic strategies targeting GPCRs, including biased ligands and combination therapies, are discussed. This synthesis provides a mechanistic foundation for understanding GPCR functions in PCa and identifies promising directions for future research and drug development.